2021
DOI: 10.3892/mmr.2021.12374
|View full text |Cite
|
Sign up to set email alerts
|

Roles of α‑synuclein in gastrointestinal microbiome dysbiosis‑related Parkinson's disease progression (Review)

Abstract: Parkinson's disease (PD) is the second most common neurodegenerative disease amongst the middle-aged and elderly populations. Several studies have confirmed that the microbiota-gut-brain axis (MGBA) serves a key role in the pathogenesis of PD. Changes to the gastrointestinal microbiome (GM) cause misfolding and abnormal aggregation of α-synuclein (α-syn) in the intestine. Abnormal α-syn is not eliminated via physiological mechanisms and is transported into the central nervous system (CNS) via the vagus nerve. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 191 publications
(203 reference statements)
0
20
0
Order By: Relevance
“…The gut microbiota may influence brain function and behavior through neurological, immunological, and endocrine pathways, establishing the microbiota–gut–brain axis (MGBA) [ 7 , 8 ]. Clinical investigations have shown that both the composition and abundance of gut bacteria and the produced metabolites are drastically altered in patients with PD compared to those in healthy patients [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The gut microbiota may influence brain function and behavior through neurological, immunological, and endocrine pathways, establishing the microbiota–gut–brain axis (MGBA) [ 7 , 8 ]. Clinical investigations have shown that both the composition and abundance of gut bacteria and the produced metabolites are drastically altered in patients with PD compared to those in healthy patients [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because the gut microbiota and its metabolites control neuroinflammation, barrier function, and neurotransmitter activity, it has been hypothesised that these factors contribute to the aetiology of PD. The microbiota-gutbrain axis may offer a route for the transmission of misfolded a-synuclein because of the bidirectional contact between the enteric nervous system and central nervous system (CNS) in humans [10]. a-Synuclein misfolding and aberrant aggregation are caused by changes in the gastrointestinal microbiome (GM) in the intestine, especially an increase in pathogenic bacteria such as Enterobacteriaceae that produce curli proteins and abnormal amyloids.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in Prevotellaceae in PD patients may be related to the reduction in mucin production defining an amplified intestinal permeability, known also as "leaky gut", that can be associated with α-synuclein aggregates through the bacteria translocation and the production of bacterial products that induce inflammation [88] (i.e., gut-derived lipopolysaccharide (LPS) that can support the impairment of the blood-brain barrier [89]) and the reactive oxygen species production in the GI system thus starting the α-synuclein accumulation at the level of ENS [90]. In an in vivo study, using rats injected at the level of substantia nigra with LPS, an induction of inflammation was observed, leading to damage of the nigrostriatal dopaminergic neurons, thus suggesting that this event could be implicated in neurodegeneration processes [91].…”
Section: Gut Microbiota and Pdmentioning
confidence: 99%